Ameliorative effects of riboflavin on acetic acid-induced colonic injury in rats - ERTAŞ, BÜŞRA; AKAKIN, DİLEK; ŞENER, GÖKSEL; YÜKSEL, MERAL (WILEY, 2018)
Riboflavin (RF) has been found to be a promising antioxidant and/or anti-inflammatory agent in several studies. However, the effect of RF against acetic acid (AA)-induced colonic injury is currently unknown. This study aimed to investigate the potential antioxidant and protective effects of RF in a rat model of ulcerative colitis. Starting immediately after the colitis induction (AA+RF group) or 1week before the colitis induction (RF+AA+RF group), the rats were treated with RF (25mg/kg per day; p.o.) for 3days. The control and AA groups received saline (1mL; p.o.) whereas AA+SS group (positive control) received sulfasalazine (100mg/kg per day; p.o.) for 3days. Colonic samples were taken for the biochemical and histological assessments on the third day. High damage scores, elevated tissue wet weight index (WI), tissue myeloperoxidase (MPO) activity, 8-hydroxy-2-deoxyguanosine levels and chemiluminescence values, and a pronounced decrease in antioxidant glutathione (GSH) levels of the AA group were all reversed by RF pretreatment (RF+AA+RF group) and SS treatment (AA+SS group) (P<.05-.001). Tissue WI, MPO activity and GSH levels were not statistically changed in the AA+RF group. Western blot analysis revealed that the decreased protein expressions of tissue collagen (COL) 1A1, COL3A1 and transforming growth factor-1 in the AA group were elevated in all the treatment groups (P<.05-.001). In conclusion, RF exerts both the antioxidant and anti-inflammatory effects against AA-induced colonic inflammation by suppressing neutrophil accumulation, inhibiting reactive oxidant generation, preserving endogenous glutathione, improving oxidative DNA damage and regulating inflammatory mediators, suggesting a future potential role in the treatment and prevention of ulcerative colitis.
Keywords: acetic acid; colitis; oxidative damage; riboflavin; INFLAMMATORY-BOWEL-DISEASE; ULCERATIVE-COLITIS; DNA-DAMAGE; OXIDATIVE STRESS; TNF-ALPHA; GROWTH; BETA; ACTIVATION; EXPRESSION; CELLS